(3GdYdGbGJ GdJLGQjI ddeZQH GdChSW (B/s - (3HTGQj, dWjaIs ((3GdLRGFQ (B: s (3efThQGJ hRGQI GdTDhf GdOjfjI hGdChbGa(B, s, 2011)
(3jVe JdeSGf bGYOI GdeZQH GdChSW, Gdfbd GdJLGQj Hjf EeGQI JdeSGf hGdHdOGf GdeJYGedI eYgG, GdMQcI GdJLGQjI Hjf EeGQI Hfj YHO GdhGO hHYV HdOGf GdYGde, GdeeGQSI GdJLGQjI aj OhdI Hfj YHO GdhGO, JfXje GdJLGQI(B.s
(3HjHdjhZQGajG(B: (3U U(B.285-302s
Keywords: (3GdJLGQIs; (3Gdfbds